Axitinib and HDAC Inhibitors Interact to Kill Sarcoma Cells - Roberts, Jane L.; Booth, Laurence; Poklepovic, Andrew; Dent, Paul (Frontiers in Oncology, 2021)
We have extended our analyses of HDAC inhibitor biology in sarcoma. The multi-kinase inhibitor axitinib interacted with multiple HDAC inhibitors to kill sarcoma cells. Axitinib and HDAC inhibitors interacted in a greater than additive fashion to inactivate AKT, mTORC1 and mTORC2, and to increase Raptor S722 / S792 phosphorylation. Individually, all drugs increased phosphorylation of ATM S1981, AMPK alpha T172, ULK1 S317 and ATG13 S318 and reduced ULK1 S757 phosphorylation; this correlated with enhanced autophagic flux. Increased phosphorylation of ULK1 S317 and of Raptor S722 / S792 required ATM-AMPK signaling. ULK1 S757 is a recognized site for mTORC1 and knock down of either ATM or AMPK alpha reduced the drug-induced dephosphorylation of this site. Combined exposure of cells to axitinib and an HDAC inhibitor significantly reduced the expression of HDAC1, HDAC2, HDAC3, HDAC4, HDAC6 and HDAC7. No response was observed for HDACs 10 and 11. Knock down of ULK1, Beclin1 or ATG5 prevented the decline in HDAC expression, as did expression of a constitutively active mTOR protein. Axitinib combined with HDAC inhibitors enhanced expression of Class I MHCA and reduced expression of PD-L1 which was recapitulated via knock down studies, particularly of HDACs 1 and 3. In vivo, axitinib and the HDAC inhibitor entinostat interacted to significantly reduce tumor growth. Collectively our findings support the exploration of axitinib and HDAC inhibitors being developed as a novel sarcoma therapy.